Peran Guru Pendidikan Agama Islam dalam Pembinaan Akhlak Siswa di SMK Matsna Karim Diwek Jombang - Musli’ah Musli’ah; Ahsanatul Khulailiyah; Nurul Lailiyah (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2022)
The aims of this research are 1). to describe students' morals to others and students' morals to teachers at SMK Matsna Karim Diwek Jombang 2). describe the role of teachers as educators and mentors in fostering students' morals at SMK Matsna Karim Diwek Jombang. This research is a qualitativefield research, the form of the research is descriptive qualitative using data collection techniques, namely observation, interviews, and documentation. Furthermore, data analysis was carried out using descriptive qualitative analysis. The results showed that: 1.) Morals of students to others at SMK Matsna Karim Diwek Jombang include: respecting fellow friends, greeting each other, and helping to help but there are some students who lack morals such as: not participating in religious activities, still sitting around in the canteen during class hours while the morals of students to teachers at the Matsna Karim Diwek Jombang Vocational School include: greeting the teacher, being obedient to the teacher, speaking politely to the teacher, paying attention to the teacher and discipline but there are some who lack morals such as: not participating in religious activities, still sitting in the cafeteria during class hours. 2.) The role of Islamic religious education teachers in fostering the morals of students at SMK Matsna Karim Diwek Jombang, focused on two roles, namely: As educators, teachers as educators at SMK Matsna Karim such as teaching how to read the Qur'an, how to speak well to anyone, admonishing students when speaking badly and reminding students to perform worship on time and as a guide in moral development by holding habituation of religious activities, namely dhuha prayer in congregation, dhuhur prayer in congregation, reading the Qur'an, Istiqosah, and the observance of Islamic holidays.